Semiotics in Signs, Symbols and Brands (Semiotika dalam “tanda”, simbol dan merek) - Ludwig Suparmo (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2017)
Modern day science on Semiotics, not only study ‘signs’ - it goes much deeper than that - the study goes further into how meaning is formed. The study goes on how people first of all interpreted a sign, how they then draw on cultural or personal experience to understand a sign. In that sense semiotics is about communication. Whilst in communication signs and symbols are common tools, signs and symbols can take different forms. Generally, it is an object representing another to give it an entirely different meaning that is much deeper and more significant. The paper is a qualitative research based discussions on some of the signs and symbols which the writer is curious in exploring further after his studies about brands and branding. Understanding through semiotics, some most common signs and symbols are interestingly revealed. During the research heraldry and coats of arms came to the picture. The study hopes to enlighten academics and practitioners in graphic design and advertising as well as marketing to understand better about branding and communication. The article also found out suggestions of some basic hints on how to design meaningful symbols.